A web-based educational information system for urban agriculture management as a solution to urban land conversion - Arista, Nor Isnaeni Dwi; Himawan, Rifqi; Pratama, Rizhal Akbar Jaya (Social Agriculture, Food System, and Environmental Sustainability, 2025)
Background: Urban industrial development is directly correlated with population density. Data from BPS (Statistics Indonesia) during 1998-2002 indicates a significant conversion of agricultural land to non-agricultural purposes, approximately ±110,000 hectares annually. This highlights the inevitability of urban infrastructure development. As urban expansion reduces agricultural land, population density and food security needs inversely correlate with current land availability. Methods: This research uses problem identification, literature review, potential analysis, and strategy design methodology to address agricultural challenges in urban settings. Finding: Based on these challenges, we propose the "Soperku (My Agricultural Solution)" website as an innovative solution. Soperku is an internet-integrated platform that facilitates knowledge exchange about urban agriculture preservation and agricultural entrepreneurship. The platform implements urban farming concepts such as vertical farming, hydroponics, and rooftop gardening for urban residences. A key feature is the involvement of competent stakeholders, ensuring the validity of information through a triple helix model, which includes academics, business practitioners, and government entities. These stakeholders collaborate within an integrated framework of information chains, public services, and product marketing. Academic institutions can disseminate research through the Soperku platform, while government support is crucial in creating favorable economic regulations to attract agricultural businesses. Conclusion: The Soperku website aims to provide educational services to society and foster agricultural environments in urban industrial settings, making it easier to learn and implement agricultural practices. This initiative benefits younger generations who will become future drivers of Indonesia's economy. Novelty/Originality: By integrating triple helix stakeholders and modern agricultural techniques, Soperku offers a novel approach to maintaining agricultural practices in increasingly urbanized environments.